Tinjauan Atas Prosedur Persediaan Barang Dagang pada PT. Perkebunan Nusantara VIII Unit Industri Hilir Teh Bandung - Sukanda, Rini Septiani; Yulianti, Yuni (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2017)
PT. Perkebunan Nusantara VIII Unit Industri Hilir Teh Bandung Tea Industry is a company engaged in the field of tea processing end, where the production of the results will be used as trade goods inventory. Inventory is one of the assets of the smooth running of operational activities to support companies that trade goods goods inventory at any time fixed would be sure in order for sales activities. A problem that often occurs is the buildup of in the warehouse items so that items being damaged, and the possibility of goods being expired. The purpose of this research was conducted to find out how the application of the procedures and know the merchandise inventory constraints as well as the efforts made by PT. Perkebunan Nusantara VIII Unit Industri Hilir The Bandung. The research method used is descriptive method, by mean of observation and interviews as well as the study of librarianship. Based on the results of the study it can be concluded that the application of the procedure of trade goods inventory include the admission procedure of trademark part production, storage of goods and merchandise spending.